Artificial Intelligence in Corporate Financial Communication - Okonkwo Doris Ngozi; Oreoluwa Blessing Omojola; Daga Dogara James; Adeniyi Akinwumi John (Britain International for Academic Research (BIAR-Publisher), 2026)
Financial reporting was enhanced by Artificial Intelligence (AI), which served as a communication channel enabling investors to make informed investment decisions. Financial reports acted as a window through which investors assessed the financial performance of an organization. AI had become a transformative force in corporate financial communication, reshaping how organizations collected, analyzed, and disseminated financial information. Financial reporting, which served as a vital communication tool between companies and investors, was increasingly strengthened by AI to ensure accuracy, timeliness, and transparency. Technologies such as Machine Learning (ML), Natural Language Processing (NLP), and Robotic Process Automation (RPA) had emerged as powerful tools that enhanced the efficiency and reliability of financial reporting and investor relations. The objective of this study was to examine the impact of AI on corporate financial communication, emphasizing its role in improving financial reporting quality, investor engagement, and decision-making. The study adopted a qualitative research design and employed a systematic review of relevant literature, including peer-reviewed journal articles, industry publications, and case studies that explored the application of AI in financial management and communication. Data was analyzed thematically to identify the major trends, opportunities, and challenges associated with AI adoption in financial reporting. The study provided insights into how AI technologies could be effectively integrated into financial communication practices while maintaining ethical standards, data transparency, and human oversight.